2014
DOI: 10.3109/01913123.2014.893045
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Microcystic Stromal Tumor: Report of A New Entity with Immunohistochemical and Ultrastructural Studies

Abstract: Microcystic stromal tumor is a recently described rare subtype of ovarian tumor for which there has been no previously reported ultrastructural study. We report a case with the characteristic histological and immunohistochemical features and the first ultrastructural study. The immunohistochemical findings of strong and diffuse nuclear staining for beta catenin and P27 are suggestive of dysregulation of more than one genetic pathway. The ultrastructural findings are supportive of the previous postulation of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 14 publications
2
23
1
Order By: Relevance
“…In the present study, we report six new cases of MCST, in addition to the one reported previously . Based on the current report in combination with previous publications, we conclude that ovarian MCST is a unique entity with distinct features among ovarian neoplasms. Although there is some morphological overlap with other ovarian neoplasms, the characteristic morphology of MCST comprises variable‐sized microcysts, frequent hyalinized stromal plaques and bland round‐to‐ovoid cells.…”
Section: Discussionsupporting
confidence: 80%
“…In the present study, we report six new cases of MCST, in addition to the one reported previously . Based on the current report in combination with previous publications, we conclude that ovarian MCST is a unique entity with distinct features among ovarian neoplasms. Although there is some morphological overlap with other ovarian neoplasms, the characteristic morphology of MCST comprises variable‐sized microcysts, frequent hyalinized stromal plaques and bland round‐to‐ovoid cells.…”
Section: Discussionsupporting
confidence: 80%
“…None of 14 tumors harbored the FOXL2 402C > G mutation that is frequently seen in adult granulosa cell tumor. 4 …”
Section: Molecular Resultsmentioning
confidence: 99%
“…These findings further establish that the tumorigenesis of MST involves dysregulation of the Wnt/b-catenin pathway. [2][3][4]28 b-catenin has a key role in cell-cell adhesion and binds to the cytoplasmic region of E-cadherin and acatenin at adherens junctions. 28 b-catenin also plays a critical role in the transduction of Wnt signals; in the absence of Wnt signaling, b-catenin joins a destruction complex, where it undergoes CK1a and GSK-3b phosphorylation and is subsequently degraded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations